Biomedicina E Farmácia: Aproximações 2 2019
DOI: 10.22533/at.ed.23119150419
|View full text |Cite
|
Sign up to set email alerts
|

CARACTERIZAÇÃO ANATÔMICA E HISTOQUÍMICA DA LÂMINA FOLIAR DE Calotropis procera (Aiton) W.T.Aiton

Abstract: DIABETES CONTROL AND COMPLICATION STRIALRESEARCH GROUP. The effect of intensive treatment of diabetes on the development and progression of long-term complications in insulindependent diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 154 publications
(205 reference statements)
0
5
0
Order By: Relevance
“…(Sethi, 2014), C. roseus (Pacheco, 1980; Abdalla et al, 2016), H. lancifolius , H. sucuuba (Larrosa & Duarte, 2005; Baratto et al, 2010), L. reticulata (Ramesh et al, 2014), M. coccinea (Duarte & Larrosa, 2011), and for the species of Forsteronia (Rio et al, 2005; Larrosa & Duarte, 2006) and Geissospermum (Silva et al, 2018). According to Metcalfe & Chalk (1950), this is the most common type of mesophyll in Apocynaceae, and isobilateral mesophyll may rarely occur, as was found in C. procera by Sá et al (2019) and in N. oleander by Abdalla et al (2016). Carvalho et al (2017) reported the presence of isofacial co-occurring with dorsiventral mesophyll in different specimens of M. odorata .…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…(Sethi, 2014), C. roseus (Pacheco, 1980; Abdalla et al, 2016), H. lancifolius , H. sucuuba (Larrosa & Duarte, 2005; Baratto et al, 2010), L. reticulata (Ramesh et al, 2014), M. coccinea (Duarte & Larrosa, 2011), and for the species of Forsteronia (Rio et al, 2005; Larrosa & Duarte, 2006) and Geissospermum (Silva et al, 2018). According to Metcalfe & Chalk (1950), this is the most common type of mesophyll in Apocynaceae, and isobilateral mesophyll may rarely occur, as was found in C. procera by Sá et al (2019) and in N. oleander by Abdalla et al (2016). Carvalho et al (2017) reported the presence of isofacial co-occurring with dorsiventral mesophyll in different specimens of M. odorata .…”
Section: Discussionmentioning
confidence: 83%
“…In the investigation by Trindade et al (2016), the histochemical tests for tannins and starch grains were negative in A. excelsum . Sá et al (2019) also obtained a negative histochemical test for tannins in the leaf blade of C. procera , but observed starch grains in the parenchyma of the midrib, the same place where starch grains were observed in H. speciosa .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations